2019
DOI: 10.1101/696070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interaction of a sarcolipin pentamer and monomer with the sarcoplasmic reticulum calcium pump, SERCA

Abstract: The sequential rise and fall of cytosolic calcium underlies the contraction-relaxation cycle of muscle cells. While contraction is initiated by the release of calcium from the sarcoplasmic reticulum, muscle relaxation involves the active transport of calcium back into the sarcoplasmic reticulum. This re-uptake of calcium is catalysed by the sarco-endoplasmic reticulum Ca 2+ -ATPase (SERCA), which plays a lead role in muscle contractility. The activity of SERCA is regulated by small membrane protein subunits, m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This study evaluated the structural dynamics of the pentameric complex, the SLN channel, with either a mutation or protonation of an amino acid. Pentameric channels are formed by self‐assembly and affect the ion permeability and anion selectivity under certain conditions 19,21 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study evaluated the structural dynamics of the pentameric complex, the SLN channel, with either a mutation or protonation of an amino acid. Pentameric channels are formed by self‐assembly and affect the ion permeability and anion selectivity under certain conditions 19,21 …”
Section: Resultsmentioning
confidence: 99%
“…Our previous works also suggested that the SLN monomers assembled into a stable oligomer by forming a repeated Leu‐Ile zipper in the TM region 20 . The channel‐like pentameric protein structure was visualized by cryo‐electron microscopy and FRET 21 . In the pentameric SLN channel structure, the pore has a hydrophilic‐inward surface that allows hydroxyl groups to interact positively with the infiltrated water molecules 22 .…”
Section: Introductionmentioning
confidence: 99%
“…All these data on PLB could suggest that the same kind of interplay between SLN oligomerisation, palmitoylation and phosphorylation for inhibition of SERCA1a is present. Oligomerisation of SLN was recently proposed as a mechanism for SERCA1a regulation relying on the reduction of the interaction of both proteins similarly to PLB 55,56 . Even if the data presented in Fig.…”
Section: (In Press)mentioning
confidence: 99%
“…PLB:Cys 36 is a residue predicted to be at the membrane interface as SLN:Cys9 3,15 . Sarcolipin also forms oligomers in detergent micelles, liposomes 57 and membranes 56 . Phosphorylation of SLN:Thr5 results in a loss of inhibition of SERCA1a 58 .…”
Section: (In Press)mentioning
confidence: 99%
“…These data emphasize the role of M3 as a important site for PLB binding. Binding to M3 of SERCA has been observed for both PLB (29) and SLN (44) and is hypothesized to play a role in regulating the maximal activity (Vmax) of SERCA (45,46).…”
Section: Docking Of Plb To Different Enzymatic States Of Sercamentioning
confidence: 99%